"Leaving Was a Process, Not an Event": The Lived Experience of Dating and Domestic Violence in 140 Characters. Issue 11 (June 2021) - Storer, Heather L.; Rodriguez, Maria; Franklin, Roxanne
One of the most frequent refrains heard in the public discourse on intimate partner violence (IPV) is why do they stay? The literature has demonstrated that IPV victims face multiple barriers to safely exiting their relationships. Currently, there has been a limited examination of the role social media can play in elucidating the lived experience of IPV. With 25% of the population using Twitter, there are opportunities to examine its utility for deepening understandings of IPV. Using data generated from the #WhyIStayed Twitter campaign, the purpose of this study is to examine Twitter users' reasons for staying in their abusive relationships. The study sample ( n = 3, 086) is composed of a random sample of 61, 725 English speaking tweets globally that employed the #WhyIStayed and #WhyILeft hashtags. We analyzed all tweets using thematic content analysis methods. This process involved multiple rounds of coding. In response to #WhyIStayed, Tweeters worldwide shared the barriers they faced that made leaving their abusive partners difficult. Seven primary themes emerged that influenced their decision-making processes: (a) impact of IPV on personal well-being, (b) lack of awareness regarding the dynamics of abusive relationships, (c) not identifying as a stereotypical IPV victim, (d) fear of reinforcing racial stereotypes, (e) internalizing social scripts regarding relationships, (f) structural barriers, and (g) leaving takes time. Twitter messages have the capacity to function as micronarratives that recount the complex barriers IPV victims confront when negotiating their relationships. This analysis provides a multifaceted description of the challenges associated with leaving abusive relationships that can augment existing theoretical frameworks on victim readiness. Furthermore, these findings demonstrate the myriad ways that societal representations of domestic violence (DV) serve as impediments for victims leaving their abusive relationships. Therefore, social media has the potential to provide a platform for capturing the lived experience of IPV.